Impacts of climate change on hydrology, water quality and crop productivity in the Ohio-Tennessee River Basin - Panagopoulos, Yiannis; Gassman, Philip W.; Arritt, Raymond W.; Herzmann, Daryl E.; Campbell, Todd D.; Valcu, Adriana; Jha, Manoj K.; Kling, Catherine L.; Srinivasan, Raghavan; White, Michael; Arnold, Jeffrey G. (International Journal of Agricultural and Biological Engineering, 2015)
Nonpoint source pollution from agriculture is the main source of nitrogen and phosphorus in the stream systems of the Corn Belt region in the Midwestern US. The eastern part of this region is comprised of the Ohio-Tennessee River Basin (OTRB), which is considered a key contributing area for water pollution and the Northern Gulf of Mexico hypoxic zone. A point of crucial importance in this basin is therefore how intensive corn-based cropping systems for food and fuel production can be sustainable and coexist with a healthy water environment, not only under existing climate but also under climate change conditions in the future. To address this issue, a OTRB integrated modeling system has been built with a greatly refined 12-digit subbasin structure based on the Soil and Water Assessment Tool (SWAT) water quality model, which is capable of estimating landscape and in-stream water and pollutant yields in response to a wide array of alternative cropping and/or management strategies and climatic conditions. The effects of three agricultural management scenarios on crop production and pollutant loads exported from the crop land of the OTRB to streams and rivers were evaluated: (1) expansion of continuous corn across the entire basin, (2) adoption of no-till on all corn and soybean fields in the region, (3) implementation of a winter cover crop within the baseline rotations. The effects of each management scenario were evaluated both for current climate and projected mid-century (2046-2065) climates from seven global circulation models (GCMs). In both present and future climates each management scenario resulted in reduced erosion and nutrient loadings to surface water bodies compared to the baseline agricultural management, with cover crops causing the highest water pollution reduction. Corn and soybean yields in the region were negligibly influenced from the agricultural management scenarios. On the other hand, both water quality and crop yield numbers under climate change deviated considerably for all seven GCMs compared to the baseline climate. Future climates from all GCMs led to decreased corn and soybean yields by up to 20% on a mean annual basis, while water quality alterations were either positive or negative depending on the GCM. The study highlights the loss of productivity in the eastern Corn Belt under climate change, the need to consider a range of GCMs when assessing impacts of climate change, and the value of SWAT as a tool to analyze the effects of climate change on parameters of interest at the basin scale.Keywords: agricultural management scenarios, corn-based systems, global circulation models, hydrology, water quality, crop yields, SWAT, Ohio-Tennessee River BasinDOI: 10.3965/j.ijabe.20150803.1497 Online first on [2015-03-19]Citation: Panagopoulos Y, Gassman P W, Arritt R W, Herzmann D E, Campbell T D, Valcu A, et al. Impacts of climate change on hydrology, water quality and crop productivity in the Ohio-Tennessee River Basin. Int J Agric & Biol Eng, 2015; 8(3): 36－53.